Penguatan Organisasi IJTI melalui Komunikasi Grup Chat Whatsapp dimasa Pandemi Covid-19 - herik kurniawan (Jurnal Spektrum Komunikasi, 2020)
Indonesia and the world have been hit hard by the Covid-19 pandemic. All aspects of life are disturbed and are required to make adjustments in order to survive. Likewise, the Indonesian Television Journalists Association (IJTI). The pandemic makes the entire work plan have to change. On the other hand, organizational strengthening must be carried out so that the existence of the organization is maintained. The step that was then taken was to make more use of the group features on WhatsApp social media. This feature is used to intensify communication within the organization so that the main goal of the organization, namely increasing professionalism, can still be done. This study uses a qualitative descriptive method approach, with data collection techniques, namely interview and participatory observation of the WhatsApp chat group "Pengda and Korda IJTI". Interviews were conducted on six sources who joined the WhatsApp Pengda and Korda IJTI chat group. The results showed that the WhatsApp Pengda and Korda IJTI groups carried out control, motivation, emotional and information functions in strengthening organizations in the midst of the Covid-19 pandemic.